PENINGKATAN KUALITAS PENDIDIKAN ( PERSPEKTIF MANAJEMEN PENDIDIKAN ISLAM ) - Mubin, Abd. Halim (Institut Agama Islam Negeri (IAIN) Palu, 2006)
The enhancement of education quality is a complicated effort related to various things such as the formulation of a basic concept ofÂ education that can be implemented into theÂ concept of Islamic education management, oriented to the prophetâs education. The purpose is to result in Islamic young generations Â Â who are fear to God, Â independent and compatative. For this puprpose, we need an effective school management, technical competence of education manager, enhancement of basic skills of teachers, leadership and supervision as a management service and accountability in education.Kata Kunci: Â Kualitas pendidikan, manajemen pendidikan Islam, kepemimpinan, supervisi